2018
DOI: 10.1007/s12289-018-1446-z
|View full text |Cite
|
Sign up to set email alerts
|

Enabling sheet hydroforming to produce smaller radii on aerospace nickel alloys

Abstract: This paper presents the first academic study of a hydroforming process known as edging. An edging process allows a smaller radius to be produced with a lower pressure than a standard sheet hydroforming process and is currently developed by trial and error that relies heavily on operator experience. This paper reports the first systematic investigation of the edging process that concludes in a new analytical model which can be used to enable the design of edging processes. It was found that in each of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Subsequent operations, annealing or pressure intensifiers can help tighten up the radii after the forming operation, but as a general rule keeping radii at least 3 to 5 times larger than the material thickness is advisable whenever possible for high pressure hydroforming operations, [12] and 10 times larger for low pressure operations [4]. That said, more recent work has shown that in certain circumstances the edging technique [89] or a subsequent coining operation can produce radii as small as 2 times the material thickness in certain circumstances (explained in detail in "Advanced hydroforming techniques"section).…”
Section: Sharp Radiimentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent operations, annealing or pressure intensifiers can help tighten up the radii after the forming operation, but as a general rule keeping radii at least 3 to 5 times larger than the material thickness is advisable whenever possible for high pressure hydroforming operations, [12] and 10 times larger for low pressure operations [4]. That said, more recent work has shown that in certain circumstances the edging technique [89] or a subsequent coining operation can produce radii as small as 2 times the material thickness in certain circumstances (explained in detail in "Advanced hydroforming techniques"section).…”
Section: Sharp Radiimentioning
confidence: 99%
“…This technique, as described by Triform presses (an equipment vendor) is called edging and allows for extra material to stretch in from the flange on the upwards stroke and be pushed into the corner when the punch travels back down. Bell et al showed that a flange radius could be reduced significantly by using the edging process and provided an empirically derived equation for calculating flange radii [89]. Edging, unlike a coining operation, does not require extra tooling or an additional forming cycle but it is not quite as accurate or repeatable.…”
Section: Edgingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrostatic forming for sheet metal has many advantages such as improving the ability to shape complex parts, increasing surface quality, and especially suitable for shaping lightweight and thin sheet materials [12][13][14]. Because of its superiority, there have been many studies on this technology over the years with different aspects of materials, temperatures, and die structures [15][16][17][18][19][20]. In hydrostatic forming process, the workpiece is remarkably thinned because of bulging phase under the action of a high-pressure liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The working principle of this technology is shown in Figure 1. Moreover, this technology can be suitable for the shaping of a wide variety of materials, from high deformability materials, such as carbon steel material, to low deformability materials, such as stainless steel or some alloys [1,[8][9][10][11][12]. There are many impressive studies on forming technology.…”
Section: Introductionmentioning
confidence: 99%